DIURNAL VARIATION OF BLOOD PRESSURE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS WITH CARDIOVASCULAR AUTONOMIC NEUROPATHY - Sadikova Nigora Gairatovna (Western European Studies, 2025)
We examined 80 patients with type 2 diabetes mellitus. All patients underwent Holter ECG monitoring. Based on this data, patients were divided into two groups: DAN (-) and DAN (+). All patients underwent 24-hour blood pressure monitoring. The time index of systolic and diastolic blood pressure, as well as the variability of systolic and diastolic blood pressure, were higher in the DAN (+) group. A time index greater than 20% was found in 75% of patients with type 2 diabetes mellitus and DAN (+).
Keywords: Type 2 diabetes mellitus; cardiovascular diabetic autonomic neuropathy; ambulatory blood pressure monitoring